(untitled) (Herald of the National Children’s Medical Center, 2022)
This literature review presents theoretical data on the etiopathogenetic mechanisms of development and diagnosis of esophageal atresia, as well as the evolution of surgical treatment from simple to modern methods in the global community of pediatric surgeons, including specialists from the Republic of Uzbekistan.